2011
DOI: 10.2174/138920111798376914
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis Suppressors: Basic and Translational Advances

Abstract: Tumor metastasis is a main contributor to death in cancer patients. In the last years, a new class of molecules that reduces the metastatic propensity has been identified: metastasis suppressors. These proteins regulate multiple steps in the metastatic cascade, including cell invasion, survival in the vascular and lymphatic circulation, and colonization of distant organ sites. As a consequence, they are very important therapeutic targets. This review discusses our current understanding of metastasis suppressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 132 publications
0
11
0
Order By: Relevance
“…Since we have previously shown in a murine model that GPC3 acts as a metastasis suppressor [7][8][9][10], a comprehensive analysis of the molecular mechanism of GPC3 role in the development and progression of human breast cancer is eagerly awaited. We do believe that the progress in GPC3 signaling research will provide new insights to attack targets involved in metastasis, offering unique opportunities for the development of "intelligent" therapeutics, which will lead to novel alternatives to treat breast cancer patients.…”
Section: Time (Month)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since we have previously shown in a murine model that GPC3 acts as a metastasis suppressor [7][8][9][10], a comprehensive analysis of the molecular mechanism of GPC3 role in the development and progression of human breast cancer is eagerly awaited. We do believe that the progress in GPC3 signaling research will provide new insights to attack targets involved in metastasis, offering unique opportunities for the development of "intelligent" therapeutics, which will lead to novel alternatives to treat breast cancer patients.…”
Section: Time (Month)mentioning
confidence: 99%
“…Regarding mammary gland, we have reported that ectopic GPC3 expression in LM3 (a breast mammary murine GPC3 negative metastatic cell line) was able to inhibit invasion and metastasis [7]. We have determined that GPC3 plays a role in almost all steps of the metastasis cascade by inducing mesenchymal-epithelialtransition (MET), suggesting its role as a metastasis suppressor [8]. Although the GPC3 signaling mechanism is unclear, we found that murine GPC3-reexpressing cells display an inhibition of the canonical Wnt signaling as well as an activation of the non-canonical PCP pathway [9].…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis is defined as the formation of progressively growing secondary tumor foci at sites discontinuous from the primary lesion. To metastasize, carcinoma cells must reactivate a latent embryonic program called epithelial-mesenchymal transition (EMT) [ 3 ]. EMT marks the first step of the “metastasis cascade”, where epithelial cells of the primary tumor acquire mesenchymal-like traits.…”
Section: Introductionmentioning
confidence: 99%
“…Just as tumor promoters, such as oncogenic Ras or Src, play positive roles in regulating tumorigenesis, a growing body of literature demonstrates a new class of proteins, known as metastasis suppressors, that effectively inhibit metastasis [ 17 , 18 ]. Examples of metastasis suppressors include Kangai1 (KAI1/CD82), E-cadherin, Rho GDP dissociation inhibitor 2 (RhoGDI2), Src-suppressed C kinase substrate (SSeCKS) and N-myc downstream regulated gene 1 (NDRG1) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%